Benefits of Routine, Opt-Out Abortion and Family Planning Training: 20 Years of the Ryan Program [02J]. (May 2020) - Steinauer, Jody; Turk, Jema; Koenemann, Katheryn; Simonson, Kristin; Landy, Uta
Abstract : INTRODUCTION: To describe the effects of routine, opt-out abortion and family planning training on clinical exposure to uterine evacuation skills and intentions to provide abortion post-residency. METHODS: Data from the first 20 years of the Ryan Residency Training Program in Abortion and Family Planning (RP) were analyzed. Post-rotation surveys assessed residents' experiences with abortion and intentions to provide abortions post-residency. The 2019 residency program director survey assessed benefits of training from the educators' perspective. This study is considered exempt by the University of California San Francisco IRB. RESULTS: A total of 3, 197 residents completed post-rotation surveys, for an overall response rate of 80.1%. During the rotation, residents, including those who partially participated, gained significant exposure to all methods of first- and second-trimester termination, with an average of 7.4 medication abortions, 11.8 manual uterine aspirations, 15.6 electric uterine aspirations and 5.8 second-trimester dilation and evacuations (D&E). Residents reported feeling competent to do aspiration procedures independently up to an average of 12.8 weeks. Eighty-one percent of residents intend to do abortions for medical reasons after residency and sixty-one percent for all reasons. Ninety-six percent of directors reported increased clinical competence in abortion and contraception among all residents after the rotation, and 68% reported the RP training helped improve continuity of care for patients. CONCLUSION: Routine, opt-out training in abortion and family planning gives OB-GYN residents an opportunity to gain the clinical skills necessary to integrate abortion into their patient care after residency.